Container with trunnion

JP2026165499APending Publication Date: 2026-10-14HITACHI GE NUCLEAR ENERGY LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025057915
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、従来技術よりも工期を短縮することができ、製造コストも低減することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165499000001_ABST
    Figure 2026165499000001_ABST
Patent Text Reader

Abstract

We provide a trunnion-equipped container that can shorten construction time and reduce manufacturing costs compared to conventional technologies. [Solution] The trunnion-equipped container 100 has one adhesive layer 20 that fills the gap between the stainless steel constituting the trunnion 19 and the surrounding organic coating. The adhesive layer is made of a silicone rubber-based sealant. The silicone rubber-based sealant contains calcium carbonate treated with an unsaturated fatty acid, isobutyltrimethoxysilane, and diisopropoxydiititanate.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a container with trunnions.

BACKGROUND ART

[0002] After nuclear power generation, spent fuel assemblies removed from a nuclear reactor are cooled for a certain period in a cooling pool inside a nuclear power plant, and then transported to a processing facility such as a fuel reprocessing plant, an intermediate storage facility, or the like. When the generated amount of spent nuclear fuel exceeds the reprocessing capacity, it becomes necessary to store the spent nuclear fuel for a long period of time, so dry storage is being considered. When storing spent nuclear fuel inside or outside a nuclear power plant, or transporting spent nuclear fuel, a metallic dry cask, for example a spent fuel assembly storage container, is used as the container for storing the spent fuel assemblies.

[0003] Furthermore, as a container for storing various deposits containing radioactive materials generated from decommissioned reactors, for example, iron scraps, concrete, plastics, textile products and the like containing radioactive materials generated during the decommissioning process, or various filters, adsorbents and the like used to remove radioactive materials from water, seawater and the like used during the decommissioning process, a metallic container (hereinafter referred to as "radioactive material deposit storage container") is used.

[0004] Spent nuclear fuel is loaded into the spent fuel assembly storage container within the cooling pool. The spent fuel assembly storage container has trunnions on its surface. The trunnions are columnar or cylindrical protrusions attached to support the main body of the spent fuel assembly storage container and to rotate it when the container is submerged in the cooling pool. The trunnions are made of highly corrosion-resistant stainless steel. On the other hand, the main body of the spent fuel assembly storage container is made of carbon steel, and its surface is coated with an organic-based paint to ensure corrosion resistance. Furthermore, a slight gap exists between each trunnion and the main body of the spent fuel assembly storage container. An adhesive is filled to fill this gap.

[0005] Conventionally, a primer specifically designed for adhesives has been applied beneath the adhesive to enhance its bonding strength (see, for example, Patent Document 1). By controlling the primer's thickness to approximately 3 to 8 molecular layers, specifically to a film thickness of approximately 20 to 200 nanometers, strong adhesion between the underlying stainless steel or painted surface and the adhesive has been ensured. However, the application area for the primer is complex, involving combinations of different materials, and must be done manually. Moreover, because the application surface is almost vertical, the primer is prone to dripping. Therefore, applying such a thin film while controlling the film thickness requires quick application at a constant weight to a specific area, demanding considerable skill from the worker. Furthermore, applying primers containing many components that volatilize at room temperature requires weighing them on a balance and applying them in small batches to minimize weight errors, which increases the number of steps and thus the time required, placing a burden on the worker. Furthermore, even if the primer is applied slowly to the aforementioned thickness, the smooth and vertical surface of the primer can cause the adhesive to slip before it hardens, resulting in a significant deterioration of the appearance—a phenomenon known as "slippage." This phenomenon also contributes to a decrease in the adhesive strength of the caulking material. Consequently, the need for rework increases the workload and extends the construction period. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 2000-290537 [Overview of the Initiative] [Problems that the invention aims to solve]

[0007] In the prior art described in Patent Document 1, slippage is prevented by creating surface irregularities through the application of granular material. However, even with the primer composition described in Patent Document 1, it is difficult to control the primer application thickness to around 20-200 nanometers, resulting in a time-consuming application process. Furthermore, longer application times increase fixed costs, leading to higher overall costs. Therefore, there is a need for further reductions in primer application time.

[0008] The present invention was made to solve the aforementioned problems, and its main objective is to provide a trunnion-equipped container that can shorten the construction period and reduce manufacturing costs compared to the conventional technology. [Means for solving the problem]

[0009] To achieve the above objective, the present invention provides a container with a trunnion, having one adhesive layer that fills the gap between the stainless steel constituting the trunnion and the surrounding organic coating, wherein the adhesive layer is composed of a silicone rubber-based caulking material, and the silicone rubber-based caulking material comprises calcium carbonate treated with an unsaturated fatty acid, isobutyltrimethoxysilane, and diisopropoxydiititanate. Other methods will be described later. [Effects of the Invention]

[0010] According to the present invention, the construction period can be shortened and manufacturing costs can be reduced compared to the conventional technology. [Brief explanation of the drawing]

[0011] [Figure 1] This is a schematic perspective view showing a spent fuel assembly storage container as an example of a trunnion-equipped container according to this embodiment. [Figure 2A] This is a schematic cross-sectional view showing the joint between the trunnion attached to a spent fuel assembly storage container, which is an example of a trunnion-equipped container according to this embodiment, and the container body. [Figure 2B]This is a cross-sectional view schematically showing the joint portion between a trunnion attached to a spent fuel assembly storage container as an example of the trunnion-equipped container according to the present embodiment and the container main body portion. [Figure 3] This is a diagram showing the bonding portion provided in the adhesive layer of the present embodiment by chemical bonds. [Figure 4] This is a diagram showing the bonding portion of a primer provided in a conventional adhesive layer by chemical bonds. [Figure 5] This is a perspective view schematically showing a radioactive material deposit storage container as another example of the trunnion-equipped container according to the present embodiment. [Figure 6A] This is a cross-sectional view schematically showing the joint portion between a trunnion attached to a radioactive material deposit storage container as another example of the trunnion-equipped container according to the present embodiment and the container main body portion. [Figure 6B] This is a cross-sectional view schematically showing the joint portion between a trunnion attached to a radioactive material deposit storage container as another example of the trunnion-equipped container according to the present embodiment and the container main body portion. [Figure 7] This is a diagram showing the bonding portion provided in the adhesive layer of the present embodiment by chemical bonds. [Figure 8] This is a diagram showing the bonding portion of a primer provided in a conventional adhesive layer by chemical bonds. [Figure 9] This is a diagram showing the shape of a test piece when determining the tensile shear bond strength of Example 1. [Figure 10] This is a graph showing the relationship between the amount (composition ratio %) of calcium carbonate treated with the unsaturated fatty acid of Example 1 and the shear bond strength (maximum shear stress). [Figure 11] This is a graph showing the relationship between the amount (composition ratio %) of isobutyltrimethoxysilane of Example 2 and the shear bond strength (maximum shear stress). [Figure 12] This is a graph showing the relationship between the amount (composition ratio %) of diisopropoxydi(ethoxyacetoacetyl) titanate of Example 3 and the number of curing days at which the shear bond strength (maximum shear stress) saturates. [Figure 13]This is a graph showing the relationship between the amount (composition ratio %) of diisopropoxydi(ethoxyacetylacetyl)titanate of Example 3 and the cost ratio relative to the caulking material of the prior art. [Figure 14] This is a graph showing the relationship between the dried thickness of the silicone rubber-based caulking material of the present invention of Example 4 and the number of curing days at which the shear adhesive strength (maximum shear stress) saturates. [Figure 15] This is a graph showing the relationship between the amount (composition ratio %) of calcium carbonate treated with the unsaturated fatty acid of Example 5 and the shear adhesive strength (maximum shear stress). [Figure 16] This is a graph showing the relationship between the amount (composition ratio %) of isobutyltrimethoxysilane of Example 6 and the shear adhesive strength (maximum shear stress). [Figure 17] This is a graph showing the relationship between the amount (composition ratio %) of diisopropoxydi(ethoxyacetylacetyl)titanate of Example 7 and the number of curing days at which the shear adhesive strength (maximum shear stress) saturates. [Figure 18] This is a graph showing the relationship between the amount (composition ratio %) of diisopropoxydi(ethoxyacetylacetyl)titanate of Example 7 and the cost ratio relative to the caulking material of the prior art. [Figure 19] This is a graph showing the relationship between the dried thickness of the silicone rubber-based caulking material of the present invention of Example 8 and the number of curing days at which the shear adhesive strength (maximum shear stress) saturates. [Mode for Carrying Out the Invention]

[0012] Hereinafter, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail with reference to the drawings. Each drawing is only schematically illustrated to an extent that the present invention can be sufficiently understood. Therefore, the present invention is not limited to the illustrated examples alone. In each drawing, common or similar constituent elements are denoted by the same reference numerals, and redundant descriptions thereof will be omitted.

[0013] <Spent fuel assembly storage container 11 as an example of trunnion-equipped container 100> (Container main body portion) The configuration of the trunnion-equipped container 100 according to this embodiment will be described below with reference to Figures 1 to 3. Figure 1 is a schematic perspective view showing a spent fuel assembly storage container 11 as an example of the trunnion-equipped container 100 according to this embodiment. Figures 2A and 2B are schematic cross-sectional views showing the joint portion 26 between the trunnion 19 attached to the spent fuel assembly storage container 11 as an example of the trunnion-equipped container 100 according to this embodiment and the container body. Figure 3 is a diagram showing the adhesive portion 23 provided in the adhesive layer 20 of this embodiment as being chemically bonded.

[0014] The trunnion-equipped container 100 according to this embodiment is a container equipped with an adhesive layer to fill the gap between the stainless steel constituting the trunnion 19 and the surrounding organic coating. Here, as an example, we will describe the case in which the trunnion-equipped container 100 is configured as a spent fuel assembly storage container 11 for storing spent fuel assemblies. As shown in Figure 1, the trunnion-equipped container 100 according to this embodiment has only one adhesive layer 20 that fills the gap between the stainless steel constituting the trunnion 19 and the surrounding organic coating. The adhesive layer 20 is composed of a silicone rubber-based caulking material. The silicone rubber-based caulking material is composed of calcium carbonate treated with an unsaturated fatty acid, isobutyltrimethoxysilane, and diisopropoxydi(ethoxyacetoacetyl)titanate (hereinafter sometimes simply referred to as "diisopropoxydititanate").

[0015] Figure 1 shows the internal and cross-sectional structure of a spent fuel assembly storage container 11, which has a roughly cylindrical shape, with a portion cut out. The spent fuel assembly storage container 11 comprises a container body for storing fuel assemblies (not shown) and a neutron shielding material 16 arranged around the fuel assemblies. The fuel assemblies referred to here are, for example, spent fuel assemblies, and the same applies hereafter. However, the fuel assemblies that can be stored in the spent fuel assembly storage container 11 are not limited to spent fuel assemblies.

[0016] The container body comprises a bottomed inner cylinder (inner container) 12, an outer cylinder (outer container) 13 installed outside the inner cylinder 12, and a basket 15 installed inside the inner cylinder 12 for storing fuel assemblies. The container body also comprises heat transfer fins 14, a primary lid 17, a secondary lid 18, and a trunnion 19. In the illustrated example, the neutron shielding material 16 is positioned between the inner cylinder 12 and the outer cylinder 13, inside the primary lid 17, and inside the secondary lid 18 so as to be positioned around the fuel assemblies when they are stored. The surface of the outer cylinder 13 is covered with an organic coating 13a. The neutron shielding material 16 suppresses the movement of neutrons into and out of the spent fuel assembly storage container 11 by absorbing neutrons, and is composed of the neutron shielding material 16 described later.

[0017] The inner cylinder 12 is made of carbon steel or the like to shield against gamma rays. Heat transfer fins 14 are provided on the sides of the inner cylinder 12 to dissipate heat from the fuel assembly. The heat transfer fins 14 are made of metal plates such as copper, aluminum, or alloys thereof. The sides of the inner cylinder 12 are covered by an outer cylinder 13 which is installed outside the heat transfer fins 14.

[0018] The basket 15 is installed inside the inner cylinder 12 and has a grid-like structure. The basket 15 contains fuel assemblies to be stored in the spent fuel assembly storage container 11, for example, in quantities of about 30 to 70 assemblies. The fuel assemblies are stored separated from each other by metal basket partition plates 15a arranged in a grid pattern.

[0019] The inner cylinder 12, which constitutes the main body of the spent fuel assembly storage container 11, has a primary lid 17 and a secondary lid 18 attached to an opening at the top (not shown). The fuel assemblies contained in the spent fuel assembly storage container 11 are sealed within the inner cylinder 12 by a double structure of the inner primary lid 17 and the outer secondary lid 18. A predetermined number of trunnions 19 are provided on the side of the outer cylinder 13 to support the spent fuel assembly storage container 11 on a support frame or the like, or to fix the spent fuel assembly storage container 11 to a transport lifting device or the like.

[0020] Between the inner cylinder 12 and the outer cylinder 13, multiple heat transfer fins 14 extend radially at equal intervals in the circumferential direction. The heat transfer fins 14 are spaced apart from each other, and a space is provided between the inner cylinder 12 and the outer cylinder 13, surrounding the inner cylinder 12. The primary cover 17 and the secondary cover 18 can be provided in a hollow structure while ensuring shielding performance against radiation and secondary gamma rays from the fuel assembly. The neutron shielding material 16 is placed between the inner cylinder 12 and the outer cylinder 13 and in the hollow portion of the primary cover 17, surrounding the fuel assembly.

[0021] Figures 2A and 2B are schematic cross-sectional views showing the joint 26 between the trunnion 19 attached to the spent fuel assembly storage container 11 of this embodiment and the container body. The joint 26 is bonded with an adhesive layer 20 to fill the gap between the trunnion 19 and the partition plate 21. The adhesive layer 20 is made of the silicone rubber-based sealant of this embodiment. The trunnion 19 is made of stainless steel. The partition plate 21 is connected to the outer cylinder 13 by a welded joint 22. The surfaces of the outer cylinder 13 and the welded joint 22 are covered with an organic coating 13a. The adhesive layer 20 is for bonding the interface between the organic coating 13a applied to the surfaces of the partition plate 21 and the welded joint 22 and the stainless steel trunnion 19. The adhesive layer 20 is firmly bonded by the adhesive joint 23 of this embodiment. Therefore, primer application is unnecessary.

[0022] (Construction method for joint 26) The surfaces of the stainless steel trunnion 19, the partition plate 21, and the organic coating 13a applied to the welded joint 22 are cleaned with alcohol and allowed to dry thoroughly. No primer is applied to the work surface. Masking tape is applied to areas other than the work surface to ensure a uniform application width. The adhesive layer 20 is formed by applying the silicone rubber-based sealant of this embodiment to a uniform thickness using a spatula. The coating is applied so that the thickness after drying is between 2 mm and 5 mm. After application, no heating is performed, and it is allowed to cure at room temperature.

[0023] (Adhesive portion 23 of this embodiment) Figure 3 shows the chemical bonds of the adhesive portion 23 provided on the adhesive layer 20 of this embodiment. The chemical bonds of the adhesive portion 23 are shown based on the results of examining the interface of the adhesive layer using X-ray photoelectron spectroscopy (XPS). In this embodiment, the adhesive portion 23 has two types of adherends: the stainless steel of the trunnion 19 and the organic coating 13a, so two types of chemical bonds exist. In this embodiment, since no primer is used and a specific silicone rubber-based caulking material is used, the adhesive portion 23 with the stainless steel of the trunnion 19 is composed of a strong MOR chemical bond. M is the metallic element of the stainless steel, mainly Fe. On the other hand, R is the chemical substance that constitutes the adhesive layer 20. In this embodiment, since a specific silicone rubber-based caulking material is used, R is Si. On the other hand, the adhesive portion 23 with the organic coating 13a is composed of a strong COR chemical bond. C is the carbon in the organic substance of the organic coating 13a. On the other hand, R is a chemical substance that makes up the adhesive layer 20, and since a specific silicone rubber-based caulking material is used, it becomes Si.

[0024] Figure 3 shows how molecules composed of strong MOR chemical bonds are aligned and oriented in a specific direction. Similarly, it shows how molecules composed of strong COR chemical bonds are oriented.

[0025] (Conventional adhesive joint 25 using primer and conventional silicone rubber-based sealant) Figure 4 shows the chemical bonding of the adhesive portion 25 provided on the adhesive layer 24 using a primer and a conventional silicone rubber-based sealant, unlike in this embodiment. The chemical bonding of the adhesive portion 25 is shown as a result of examining the interface of the adhesive layer using X-ray photoelectron spectroscopy. In the conventional technology, the adhesive portion 25 has two types of adherends: the stainless steel of the trunnion 19 and the organic coating 13a, so two types of chemical bonding exist. In the conventional technology, since a primer and a conventional silicone rubber-based sealant are used, the adhesive portion 25 with the stainless steel of the trunnion 19 is composed of hydrogen bonds where the MOH chemical bond and the HOR chemical bond are weakly linked to each other's OH groups. M is the metallic element of the stainless steel, mainly Fe. On the other hand, R is the chemical substance that makes up the primer in the adhesive layer 24, and is either Si or C. On the other hand, the adhesive portion 25 with the organic coating 13a is composed of hydrogen bonds where the COH chemical bond and the HOR chemical bond are weakly linked to each other's OH groups. C is the carbon in the organic substance of the organic coating 13a. On the other hand, R is a chemical substance that constitutes the primer in the adhesive layer 24, and is either Si or C. Thus, the adhesive portion 25 of the primer is bonded to both the stainless steel of the trunnion 19 and the organic coating 13a by weak hydrogen bonds between OH groups. The bond energy of the conventional adhesive portion 25 using the primer and conventional silicone rubber-based caulking material is approximately 1 / 10 of the bond energy of the adhesive portion 23 in this embodiment. Therefore, a slip phenomenon occurs in the conventional adhesive portion 25.

[0026] <An example of a trunnion-equipped container 100: a container 31 containing radioactive material> (Container body) Figure 5 is a schematic perspective view of the radioactive material deposit storage container 31 of this embodiment. Here, as another example, we will explain the case in which the trunnion-equipped container 100 is configured as a radioactive material deposit storage container 31 that stores radioactive material deposits that have unintentionally adhered to components constituting a nuclear power plant and have been removed from those components. In Figure 5, a portion of the roughly cylindrical radioactive material deposit storage container 31 is cut out to show its internal structure and cross-sectional structure. The radioactive material deposit storage container 31 comprises a container body for storing radioactive material deposits (not shown), and a neutron shielding material 36 and a partition plate 41 arranged around the radioactive material deposits. The radioactive material deposits referred to here are, for example, spent adsorbents and spent filters, and the same applies hereafter. However, the radioactive material deposits that can be stored in the radioactive material deposit storage container 31 are not limited to spent adsorbents and spent filters.

[0027] The container body comprises a bottomed inner cylinder (inner container) 32 and an outer cylinder (outer container) 33 installed outside the inner cylinder 32. The container body also includes a primary lid 37, a secondary lid 38, and a trunnion 39. The surface of the outer cylinder 33 is covered with an organic coating 33a.

[0028] The inner cylinder 32 is made of carbon steel or the like to shield against gamma rays. The radioactive materials that are stored in the radioactive material storage container 31 are stored in the inner cylinder 32, separated from each other by metal radioactive material partition plates 34.

[0029] The inner cylinder 32, which constitutes the main body of the radioactive material-contaminated container 31, has a primary lid 37 and a secondary lid 38 attached to an opening at the top (not shown). The radioactive material contained in the radioactive material-contaminated container 31 is sealed in the inner cylinder 32 by a double structure of the inner primary lid 37 and the outer secondary lid 38. A predetermined number of trunnions 39 are provided on the side of the outer cylinder 33 to support the radioactive material-contaminated container 31 on a support frame or the like, or to fix the radioactive material-contaminated container 31 to a transport lifting device or the like.

[0030] Figures 6A and 6B are schematic cross-sectional views showing the joint 46 between the trunnion 39 attached to the radioactive material-contaminated container 31 of this embodiment and the container body. The joint 46 is bonded with an adhesive layer 40 to fill the gap between the trunnion 39 and the partition plate 41. The adhesive layer 40 is made of the silicone rubber-based sealant of this embodiment. The trunnion 39 may be made of stainless steel. The partition plate 41 is connected to the outer cylinder 33 by a welded joint 42. The surfaces of the outer cylinder 33 and the welded joint 42 are covered with an organic coating 33a. The adhesive layer 40 is for bonding the interface between the organic coating 33a applied to the surfaces of the partition plate 41 and the welded joint 42 and the stainless steel trunnion 39. The adhesive layer 40 is firmly bonded at the adhesive joint 43 of this embodiment. Therefore, primer application is unnecessary.

[0031] (Construction method for joint 46) Clean the surfaces of the stainless steel trunnion 39, the partition plate 41, and the organic coating 33a applied to the welded parts 42 with alcohol and allow to dry thoroughly. Do not apply primer to the work surface. Apply masking tape to areas other than the work surface to ensure a uniform application width. Apply the silicone rubber-based sealant of this embodiment to the adhesive layer 40 using a spatula to ensure a uniform thickness. Apply so that the thickness after drying is between 2 mm and 5 mm. After application, do not heat and allow to cure at room temperature.

[0032] (Adhesive portion 43 of this embodiment) Figure 7 shows the chemical bonding of the adhesive portion 43 provided on the adhesive layer 40 of this embodiment. The chemical bonding of the adhesive portion 43 is shown as a result of examining the interface of the adhesive layer using X-ray photoelectron spectroscopy. In this embodiment, the adhesive portion 43 has two types of adherends: the stainless steel of the trunnion 39 and the organic coating 33a, so two types of chemical bonding exist. In this embodiment, since no primer is used and a specific silicone rubber-based sealant is used, the adhesive portion 43 with the stainless steel of the trunnion 39 is composed of a strong MOR chemical bond. M is the metallic element of the stainless steel, mainly Fe. On the other hand, R is the chemical substance that makes up the adhesive layer 40. In this embodiment, since a specific silicone rubber-based sealant is used, R is Si. On the other hand, the adhesive portion 43 with the organic coating 33a is composed of a strong COR chemical bond. C is C in the organic substance of the organic coating 33a. On the other hand, R is the chemical substance that makes up the adhesive layer 40, and since a specific silicone rubber-based sealant is used, it is Si.

[0033] (Conventional adhesive joint 45 using primer and conventional silicone rubber-based sealant) Figure 8 shows the chemical bonding of the adhesive portion 45 provided on the adhesive layer 44 using a primer and a conventional silicone rubber-based sealant, unlike in this embodiment. The chemical bonding of the adhesive portion 45 is shown as a result of examining the interface of the adhesive layer using X-ray photoelectron spectroscopy. In the conventional technology, the adhesive portion 45 has two types of adherends: the stainless steel of the trunnion 39 and the organic coating 33a, so two types of chemical bonding exist. In the conventional technology, since a primer and a conventional silicone rubber-based sealant are used, the adhesive portion 45 with the stainless steel of the trunnion 39 is composed of hydrogen bonds where the MOH chemical bonds and HOR chemical bonds are weakly linked to each other's OH groups. M is the metallic element of the stainless steel, mainly Fe. On the other hand, R is the chemical substance that makes up the primer in the adhesive layer 44, and is either Si or C. On the other hand, the adhesive portion 45 with the organic coating 33a is composed of hydrogen bonds where the COH chemical bonds and HOR chemical bonds are weakly linked to each other's OH groups. C is the carbon in the organic substance of the organic coating 33a. On the other hand, R is a chemical substance that constitutes the primer in the adhesive layer 44, and is either Si or C. Thus, the adhesive portion 45 of the primer is bonded to both the stainless steel of the trunnion 39 and the organic coating 33a by weak hydrogen bonds between OH groups. The bond energy of the conventional adhesive portion 45 using the primer and conventional silicone rubber-based caulking material is approximately 1 / 10 of the bond energy of the adhesive portion 43 in this embodiment. Therefore, a slip phenomenon occurs in the conventional adhesive portion 25.

[0034] The following describes various embodiments as examples of this present invention. However, the present invention is not limited to the following and can be implemented by modifying it as much as possible without significantly impairing its effects.

[0035] (Example 1) The adhesive strength of the adhesive layer applied to fill the gap between the SUS304 stainless steel and epoxy resin coating constituting the trunnion 19 in the spent fuel assembly storage container shown in Figure 1 was evaluated by a tensile shear adhesion test. Adhesion strength was defined as tensile shear adhesion strength. The specimen shape for the tensile shear adhesion test is shown in Figure 9. The test was conducted in reference to JIS K6850 (1999) "Adhesives - Test method for tensile shear adhesion strength of rigid adherends". As shown in Figure 9, the specimen was 11mm (W) x 11mm (L) x 11mm (H). t Dimensions: W11mm (height) x L12mm (width) x H12mm (thickness) t It consists of two rectangular plates, one made of SUS304 stainless steel and the other coated with epoxy resin. The two plates are joined together alternately, with a length of W11mm x width of L13mm x thickness of H13mm between them. t The shape was bonded using a silicone rubber-based sealant. The silicone rubber-based sealant in this embodiment contains calcium carbonate treated with unsaturated fatty acids, and a one-component silicone rubber-based sealant containing this in the range of 10 to 75% by weight was used. The test specimen was set in a tensile testing machine. The testing machine used was an electro-hydraulic servo-type fatigue testing machine with a capacity of ±100kN and a small load cell with a capacity of ±2kN. The test environment was a high-humidity environment with room temperature (23±5℃) and humidity of 85±5%RH. The test control was displacement control, and the test speed was 20mm / min. The test specimen was fixed using a mechanical chuck. The maximum shear stress for the tensile shear adhesion test was calculated using the following formula (1). The construction area used was the measured value. Maximum shear stress (MPa) = Maximum load Pmax (N) / Construction area An (mm²) 2 ) ... (1)

[0036] Figure 10 is a graph showing the relationship between the amount of calcium carbonate treated with unsaturated fatty acids (composition ratio %) and the shear adhesive strength (maximum shear stress). For silicone rubber-based caulking materials, an amount of calcium carbonate treated with unsaturated fatty acids (composition ratio %) in the range of 40% to 60% is preferable for high adhesive strength. Calcium carbonate treated with unsaturated fatty acids is a component that imparts superhydrophobicity, not an adhesive component. Therefore, without a primer, exceeding 60% results in insufficient adhesive strength due to insufficient adhesive components. Below 40%, the water-repellent ability decreases, and in a high-humidity environment of 85±5%RH, water seeps into the adhesive interface, resulting in insufficient adhesive strength.

[0037] (Example 2) In this embodiment, isobutyltrimethoxysilane was added to the silicone rubber-based caulking material, and a one-component silicone rubber-based caulking material containing isobutyltrimethoxysilane in the range of 2.5 to 27.5% by weight was used. The maximum shear stress of the tensile shear adhesion test was determined in the same manner as in Example 1. Figure 11 is a graph showing the relationship between the amount of isobutyltrimethoxysilane (composition ratio %) and the shear adhesion strength (maximum shear stress). The amount of isobutyltrimethoxysilane (composition ratio %) contained in the silicone rubber-based caulking material is preferably in the range of 10% to 20% for high adhesive strength. Isobutyltrimethoxysilane is a curing agent in the adhesive component. Therefore, if it is less than 10%, the curing reaction does not proceed well, and sufficient adhesive strength cannot be obtained. Furthermore, isobutyltrimethoxysilane is a water-repellent curing agent. Therefore, if it is less than 10%, the water-repellent ability decreases, and in a high-humidity environment of 85±5%RH, water seeps into the adhesive interface, and sufficient adhesive strength cannot be obtained. If the hardening rate exceeds 20%, the cured material becomes too hard and loses its elasticity, making it unable to adapt to fluctuations in the clearance between the spent fuel assembly storage container and the dissimilar material, resulting in cracking and insufficient adhesive strength.

[0038] (Example 3) In this embodiment, diisopropoxydi(ethoxyacetoacetyl) titanate is added to the silicone rubber-based sealant, and a one-component silicone rubber-based sealant containing this in the range of 2.5 to 27.5% by weight was used. The maximum shear stress in the tensile shear adhesion test was determined in the same manner as in Example 1. However, in Example 3, the test was conducted with different curing days, and the curing days at which the maximum shear stress saturated was determined. Figure 12 is a graph showing the relationship between the amount (composition ratio %) of diisopropoxydi(ethoxyacetoacetyl) titanate and the curing days at which the shear adhesion strength (maximum shear stress) saturated. Diisopropoxydi(ethoxyacetoacetyl) titanate contained in the silicone rubber-based sealant is a catalyst that speeds up the curing rate, and if its amount (composition ratio %) is less than 10%, curing takes a long time, making it impossible to cure within the target curing days of 3 days or less, thus extending the delivery date and diminishing the time-saving effect of the primerless process in the manufacture of this spent fuel assembly storage container. However, diisopropoxy di(ethoxyacetoacetyl) titanate has the disadvantage of high material costs. Figure 13 is a graph showing the relationship between the amount (composition ratio %) of diisopropoxy di(ethoxyacetoacetyl) titanate and the cost ratio compared to conventional caulking materials. When the amount (composition ratio %) of diisopropoxy di(ethoxyacetoacetyl) titanate contained in silicone rubber-based caulking materials exceeds 20%, the material cost becomes high, and the low-cost effect of primerless construction in the manufacture of this spent fuel assembly storage container is diminished. For the above reasons, the amount (composition ratio %) of diisopropoxy di(ethoxyacetoacetyl) titanate, that is, diisopropoxy dititanate, is preferably in the range of 10% to 20% for high adhesive strength.

[0039] (Example 4) In this embodiment, a one-component silicone rubber-based sealant was applied with a dried thickness ranging from 0.5 to 8 mm. Similar to Example 3, tests were conducted with varying curing times to determine the curing time at which the maximum shear stress saturated. Figure 14 is a graph showing the relationship between the dried thickness of the silicone rubber-based sealant of this embodiment and the curing time at which the shear adhesive strength (maximum shear stress) saturated. The dried thickness of the silicone rubber-based sealant of this embodiment is preferably between 2 mm and 5 mm. In applications where the adhesive layer 20 thickness exceeds 5 mm, drying takes longer, preventing curing within the target 3 days and thus extending the construction period, which is undesirable. Furthermore, in applications where the adhesive layer 20 thickness is less than 2 mm, the application thickness cannot be uniformly controlled, resulting in longer application times, which is also undesirable.

[0040] (Example 5) The adhesive strength of the adhesive layer applied to fill the gap between the SUS630 stainless steel and epoxy resin coating constituting the trunnion 39 in the radioactive material containment container shown in Figure 5 was evaluated by a tensile shear adhesion test. Adhesion strength was defined as tensile shear adhesion strength. The shape of the test specimen for the tensile shear adhesion test is shown in Figure 9. The test was conducted in reference to JIS K6850 (1999) "Adhesives - Test method for tensile shear adhesion strength of rigid adherends". As shown in Figure 9, the test specimen was W11mm (length) x L11mm (width) x H11mm (thickness). t Dimensions: W11mm (height) x L12mm (width) x H12mm (thickness) t It consists of two rectangular plates, one made of SUS630 and the other coated with epoxy resin. The two plates are joined together alternately, with a length of W11mm x width of L13mm x thickness of H13mm in between. tThe shape was bonded using a silicone rubber-based sealant. In this embodiment, calcium carbonate treated with unsaturated fatty acids was added to the silicone rubber-based sealant, and a one-component silicone rubber-based sealant containing this in the range of 10 to 75% by weight was used. The test specimen was set in a tensile testing machine. The testing machine used was an electro-hydraulic servo-type fatigue testing machine with a capacity of ±100kN and a small load cell with a capacity of ±2kN. The test environment was a high-humidity environment with room temperature (23±5℃) and humidity of 85±5%RH. The test control was displacement control, and the test speed was 20mm / min. The test specimen was fixed using a mechanical chuck. The maximum shear stress for the tensile shear adhesion test was calculated using the following formula (2). The construction area used was an actual measured value. Maximum shear stress (MPa) = Maximum load Pmax (N) / Construction area An (mm²) 2 ) ……(2)

[0041] Figure 15 is a graph showing the relationship between the amount of calcium carbonate treated with unsaturated fatty acids (composition ratio %) and the shear adhesive strength (maximum shear stress). For silicone rubber-based caulking materials, an amount of calcium carbonate treated with unsaturated fatty acids (composition ratio %) in the range of 40% to 60% is preferable for high adhesive strength. Calcium carbonate treated with unsaturated fatty acids is a component that imparts superhydrophobicity, not an adhesive component. Therefore, without a primer, exceeding 60% results in insufficient adhesive strength due to insufficient adhesive components. Below 40%, the water-repellent ability decreases, and in a high-humidity environment of 85±5%RH, water seeps into the adhesive interface, resulting in insufficient adhesive strength.

[0042] (Example 6) In this embodiment, isobutyltrimethoxysilane was added to the silicone rubber-based caulking material, and a one-component silicone rubber-based caulking material containing isobutyltrimethoxysilane in the range of 2.5 to 27.5% by weight was used. The maximum shear stress of the tensile shear adhesion test was determined in the same manner as in Example 5. Figure 16 is a graph showing the relationship between the amount of isobutyltrimethoxysilane (composition ratio %) and the shear adhesion strength (maximum shear stress). The amount of isobutyltrimethoxysilane (composition ratio %) contained in the silicone rubber-based caulking material is preferably in the range of 10% to 20% for high adhesion strength. Isobutyltrimethoxysilane is a curing agent in the adhesive component. Therefore, if it is less than 10%, the curing reaction does not proceed well, and sufficient adhesive strength cannot be obtained. Furthermore, isobutyltrimethoxysilane is a water-repellent curing agent. Therefore, if it is less than 10%, the water-repellent ability decreases, and in a high-humidity environment of 85±5%RH, water seeps into the adhesive interface, and sufficient adhesive strength cannot be obtained. If the concentration exceeds 20%, the hardened material becomes too rigid and loses its elasticity, making it unable to adapt to fluctuations in the clearance between the radioactive material-containing container and the other material, resulting in cracking and insufficient adhesive strength.

[0043] (Example 7) In this embodiment, diisopropoxydi(ethoxyacetoacetyl) titanate is added to the silicone rubber-based sealant, and a one-component silicone rubber-based sealant containing this in the range of 2.5 to 27.5% by weight was used. The maximum shear stress in the tensile shear adhesion test was determined in the same manner as in Example 5. However, in Example 7, the test was conducted with different curing days, and the curing days at which the maximum shear stress saturated was determined. Figure 17 is a graph showing the relationship between the amount (composition ratio %) of diisopropoxydi(ethoxyacetoacetyl) titanate and the curing days at which the shear adhesion strength (maximum shear stress) saturated. Diisopropoxydi(ethoxyacetoacetyl) titanate contained in the silicone rubber-based sealant is a catalyst that speeds up the curing rate, and if its amount (composition ratio %) is less than 10%, curing takes a long time, making it impossible to cure within the target curing days of 3 days or less, thus extending the delivery time and diminishing the time-saving effect of the primerless method in the manufacture of this radioactive material contamination storage container. However, diisopropoxy di(ethoxyacetoacetyl) titanate has the disadvantage of high material costs. Figure 18 is a graph showing the relationship between the amount (composition ratio %) of diisopropoxy di(ethoxyacetoacetyl) titanate and the cost ratio compared to conventional caulking materials. When the amount (composition ratio %) of diisopropoxy di(ethoxyacetoacetyl) titanate contained in the silicone rubber-based caulking material exceeds 20%, the material cost increases, and the low-cost effect of primerless construction in the manufacture of this radioactive material contamination containment container is diminished. For the above reasons, the amount (composition ratio %) of diisopropoxy di(ethoxyacetoacetyl) titanate is preferably in the range of 10% to 20% for high adhesive strength.

[0044] (Example 8) In this embodiment, a one-component silicone rubber-based sealant was applied with a dried thickness ranging from 0.5 to 8 mm. Similar to Example 7, tests were conducted with varying curing times to determine the curing time at which the maximum shear stress saturated. Figure 19 is a graph showing the relationship between the dried thickness of the silicone rubber-based sealant in this embodiment and the curing time at which the shear adhesive strength (maximum shear stress) saturated. The dried thickness of the silicone rubber-based sealant in this embodiment is preferably 2 mm to 5 mm. In applications where the adhesive layer 40 thickness exceeds 5 mm, drying takes longer, preventing curing within the target 3 days, thus extending the manufacturing time of the radioactive material containment container, which is undesirable. Furthermore, in applications where the adhesive layer 40 thickness is less than 2 mm, the application thickness cannot be uniformly controlled, resulting in longer application times, which is also undesirable.

[0045] (Example 9) To fill the gap between the SUS304 stainless steel and epoxy resin coating that make up the trunnion 19 in the spent fuel assembly storage container shown in Figure 1, commercially available Cemedyne 8051N silicone rubber-based sealant was used. No primer was used for application, and the thickness was 2 mm. The curing time was 2 days, achieving curing within the target of 3 days. Furthermore, it was confirmed that there were no problems with the adhesion of the sealant even after being submerged in a cooling pool for 10 days. The manufacturing period was shortened by 2 days compared to conventional technology, and costs were reduced by 10%.

[0046] (Example 10) To fill the gap between the SUS304 stainless steel and epoxy resin coating that make up the trunnion 19 in the spent fuel assembly storage container shown in Figure 1, commercially available Dow-Toray SE5400 silicone rubber sealant was used. No primer was used for application, and the thickness was 2 mm. The curing time was 2 days, achieving curing within the target of 3 days. Furthermore, it was confirmed that there were no problems with the adhesion of the sealant even after being submerged in a cooling pool for 10 days. The manufacturing period was shortened by 2 days compared to conventional technology, and costs were reduced by 10%.

[0047] (Example 11) To fill the gap between the SUS630 stainless steel and epoxy resin coating that make up trunnion 39 in the radioactive material containment container shown in Figure 5, commercially available Dow-Toray SE960 silicone rubber sealant was used. No primer was used for application, and the thickness was 2 mm. The curing time was 2 days, achieving curing within the target of 3 days. Furthermore, it was confirmed that there were no problems with the adhesion of the sealant even after being exposed to rain for 5 days outdoors. The manufacturing period was shortened by 2 days compared to conventional technology, and costs were reduced by 10%.

[0048] <Main features of the Trunnion-equipped container 100> The trunnion-equipped container 100 according to this embodiment can be configured to have the following features. (1) As shown in Figure 1, the container 100 with a trunnion according to this embodiment has one adhesive layer 20 that fills the gap between the stainless steel constituting the trunnion 19 and the surrounding organic coating. The adhesive layer 20 is made of a silicone rubber-based sealant. The silicone rubber-based sealant is composed of calcium carbonate treated with an unsaturated fatty acid, isobutyltrimethoxysilane, and diisopropoxydiititanate.

[0049] The trunnion-equipped container 100 according to this embodiment can exhibit sufficient adhesive strength without slippage between dissimilar materials, stainless steel and organic coating, even without the application of a primer. Furthermore, the trunnion-equipped container 100 according to this embodiment can fill the gap between the stainless steel constituting the trunnion and the surrounding organic coating with high adhesive strength, and at the same time, since the primer application process is eliminated, the construction period can be shortened and manufacturing costs can be reduced.

[0050] The trunnion-equipped container 100 according to this embodiment can shorten the construction period and reduce manufacturing costs compared to the conventional technology. Furthermore, the trunnion-equipped container 100 according to this embodiment can achieve sufficient adhesive strength to fill the gap between the stainless steel constituting the trunnion and the surrounding organic coating, even without a primer, thus improving adhesive strength. In addition, since the trunnion-equipped container 100 according to this embodiment does not require a thick adhesive layer, the drying time can be shortened. This further shortens the construction period.

[0051] (2) In the container 100 with a trunnion as described in item (1) above, the adhesive layer 20 is preferably made of a one-component silicone rubber-based sealant.

[0052] Silicone rubber-based sealants come in one-component and two-component types, with the one-component type being usable with virtually no processing. In this embodiment, the trunnion-equipped container 100 has an adhesive layer 20 made of a one-component silicone rubber-based sealant, thus reducing manufacturing effort.

[0053] (3) As shown in Figures 14 and 19, in the trunnion-equipped container 100 of item (1) above, the thickness (thickness after drying) of the adhesive layer 20 (or adhesive layer 40) is preferably 2 mm or more and 5 mm or less.

[0054] In construction where the thickness of the adhesive layer 20 (or adhesive layer 40) exceeds 5 mm, drying takes a long time, making it impossible to cure within the target curing period of 3 days or less, thus extending the construction period, which is undesirable. Also, in construction where the thickness of the adhesive layer 20 (or adhesive layer 40) is less than 2 mm, it is not possible to control the thickness uniformly, which also takes a long time, and is therefore undesirable. In the trunnion-equipped container 100 according to this embodiment, the thickness of the adhesive layer 20 (or adhesive layer 40) is between 2 mm and 5 mm, thus shortening the construction period and enabling uniform control of the thickness.

[0055] (4) As shown in Figures 10 and 15, in the trunnion-equipped container 100 of item (1) above, the amount of calcium carbonate (composition ratio %) contained in the silicone rubber-based caulking material is preferably in the range of 40% to 60%.

[0056] The trunnion-equipped container 100 according to this embodiment can achieve high adhesive strength when the amount of calcium carbonate (composition ratio %) is in the range of 40% to 60%.

[0057] (5) As shown in Figures 11 and 16, in the trunnion-equipped container 100 of item (1) above, the amount (composition ratio %) of isobutyltrimethoxysilane contained in the silicone rubber-based caulking material is preferably in the range of 10% to 20%.

[0058] The trunnion-equipped container 100 according to this embodiment can achieve high adhesive strength when the amount (composition ratio %) of isobutyltrimethoxysilane is in the range of 10% to 20%.

[0059] (6) As shown in Figures 13 and 18, in the trunnion-equipped container 100 of item (1) above, the amount (composition ratio %) of diisopropoxy di(ethoxyacetoacetyl) titanate contained in the silicone rubber-based caulking material is preferably in the range of 10% to 20%.

[0060] The trunnion-equipped container 100 according to this embodiment can achieve high adhesive strength when the amount (composition ratio %) of diisopropoxy di(ethoxyacetoacetyl) titanate is in the range of 10% to 20%.

[0061] (7) As shown in Figures 1 and 5, in the trunnion-equipped container 100 of item (1) above, the trunnion-equipped container 100 is preferably configured as a spent fuel assembly storage container 11 or a radioactive material attached container 31.

[0062] The trunnion-equipped container 100 according to this embodiment can suitably store spent fuel assemblies when configured as a spent fuel assembly storage container 11. Furthermore, the trunnion-equipped container 100 according to this embodiment can suitably store radioactive material-contaminated materials when configured as a radioactive material-contaminated material storage container 31.

[0063] As described above, the trunnion-equipped container 100 according to this embodiment can shorten the construction period and reduce manufacturing costs compared to the conventional technology.

[0064] The present invention is not limited to the embodiments described above, and includes various modifications. For example, the embodiments described above are described in detail for the purpose of clearly illustrating the present invention, and are not necessarily limited to those having all the configurations described. Furthermore, it is possible to replace some of the configurations of the embodiments with other configurations, and it is also possible to add other configurations to the configurations of the embodiments. In addition, it is possible to add, delete, or replace some of the configurations of each configuration with other configurations. [Explanation of Symbols]

[0065] 11. Spent fuel assembly storage container (cask for spent fuel storage) 12. Inner cylinder (container body) 13. Outer cylinder (container body) 13a Organic coating (container body) 14 heat transfer fins 15 Basket 15a Basket divider 16 Neutron shielding material 17 Primary lid (container body) 18 Secondary lid (container body) 19 Trunnions 20. Adhesive layer (silicone rubber-based sealant) 21 Partition plate (container body) 22. Welded parts (container body) 23 Adhesive part 24. Adhesive layer (primer and conventional silicone rubber-based sealant) 25. Adhesive joint (adhesive joint using primer and conventional silicone rubber-based sealant) 26 Joint 31. Container for storing radioactive material-contaminated items 32 Inner cylinder (container body) 33. Outer cylinder (container body) 33a Organic coating (container body) 34. Partition plate for radioactive material contamination 36 Neutron shielding material 37 Primary lid (container body) 38 Secondary lid (container body) 39 Trunnion (container body) 40. Adhesive layer (silicone rubber-based sealant) 41 Partition plate (container body) 42. Welded parts (container body) 43 Adhesive part 44. Adhesive layer (primer and conventional silicone rubber-based sealant) 45. Adhesive joint (adhesive joint using primer and conventional silicone rubber-based sealant) 46 Joint 100 Container with trunnion

Claims

1. The trunnion has one adhesive layer that fills the gap between the stainless steel constituting the trunnion and the surrounding organic coating. The adhesive layer is composed of a silicone rubber-based caulking material. The aforementioned silicone rubber-based caulking material comprises calcium carbonate treated with an unsaturated fatty acid, isobutyltrimethoxysilane, and diisopropoxydiititanate. A container with a trunnion, characterized by the following features.

2. The adhesive layer is composed of a one-component silicone rubber-based sealant. A container with a trunnion according to feature 1.

3. The thickness of the adhesive layer is 2 mm or more and 5 mm or less. A container with a trunnion according to feature 1.

4. The amount of calcium carbonate contained in the silicone rubber-based caulking material is in the range of 40% to 60%. A container with a trunnion according to feature 1.

5. The amount of isobutyltrimethoxysilane contained in the silicone rubber-based caulking material is in the range of 10% to 20%. A container with a trunnion according to feature 1.

6. The amount of diisopropoxydititanate contained in the silicone rubber-based caulking material is in the range of 10% to 20%. A container with a trunnion according to feature 1.

7. The trunnion-equipped container is configured as a spent fuel assembly storage container or a container for storing radioactive material. A container with a trunnion according to feature 1.

Citation Information

Patent Citations

  • Primer composition and sealing application using same

    JP2000290537A